Gut microbiota and autoimmune neurologic disorders: a two-sample bidirectional Mendelian randomization study - Zhang, Mengyuan; Fang, Jie; Zheng, Chamou; Lin, Qing; Zhang, Jiawei (Frontiers in Microbiology, 2024)
Background Increasing evidence has suggested that alterations in the gut microbiome are correlated with autoimmune neurologic disorders, yet the causal relationship between them has yet to be established. Methods From the published genome-wide association study (GWAS) summary statistics, we obtained data on the gut microbiota and three autoimmune neurologic disorders (Multiple Sclerosis, Guillain-Barré Syndrome, and Myasthenia Gravis). We then implemented a two-sample Mendelian Randomization (MR) to determine the causal relationship between the gut microbiota and the diseases. To validate the results, we conducted a series of sensitivity analyses. Finally, to verify the direction of causality, a reverse-causality analysis was done. Results We discovered that a higher relative abundance of the genus Ruminococcus2 (OR: 1.213, 95% CI: 1.006–1.462, p = 0.043, PFDR = 0.048) and the genus Roseburia (OR: 1.255, 95% CI: 1.012–1.556, p = 0.038, PFDR = 0.048) were associated with a higher risk of MS. Furthermore, the higher the abundance of the class Mollicutes (OR: 3.016, 95% CI: 1.228–7.411, p = 0.016, PFDR = 0.021), the genus Eubacterium (hallii group) (OR: 2.787, 95% CI: 1.140–6.816, p = 0.025, PFDR = 0.025), and the phylum Tenericutes (OR: 3.016, 95% CI: 1.228–7.411, p = 0.016, PFDR = 0.021) was linked to a greater probability of GBS. Additionally, the higher the abundance of the genus Ruminococcaceae UCG005 (OR: 2.450, 95% CI: 1.072–5.598, p = 0.034, PFDR = 0.036), the genus Holdemania (OR: 2.437, 95% CI: 1.215–4.888, p = 0.012, PFDR = 0.024), genus Lachnoclostridium (OR: 3.681, 95% CI: 1.288–10.521, p = 0.015, PFDR = 0.025) and the genus Eubacterium (ruminantium group) (OR: 2.157, 95% CI: 1.211–3.843, p = 0.003, PFDR = 0.016) correlated with a greater chance of MG occurrence. No SNPs were identified as outliers through sensitivity analysis. Then, the results of the reverse MR analysis did not indicate any reverse causality. Conclusion Our findings demonstrate a causal relationship between the gut microbiota and three autoimmune neurologic disorders, providing novel insights into the mechanisms of these autoimmune neurologic disorders that are mediated by gut microbiota.